LAMB1 promotes proliferation and metastasis in nasopharyngeal carcinoma and shapes the immune-suppressive tumor microenvironment - Enzi Feng; Xinyu Yang; Jie Yang; Qianqian Qu; Xiaojiang Li (Brazilian Journal of Otorhinolaryngology)
Objective: Laminin subunit Beta-1 (LAMB1), a component of the extracellular matrix, has been reported to be implicated in the development and progression of cancer. However, the role of LAMB1 in Nasopharyngeal Carcinoma (NPC) remains unknown. Methods: Three NPC datasets were utilized to identify LAMB1 as a targeted gene. The correlation between LAMB1 expression and clinical characteristics, prognosis was explored. KEGG and GO enrichment analyses were conducted to investigate LAMB1’s functions in NPC. The CIBERSORT, xCell, MCPCOUNTER, and EPIC methods were used to assess the Cancer-Associated Fibroblasts (CAFs) and immune cells infiltration. We predicted LAMB1’s effect on treatment using TIDE, CTRP, and CellMine databases. Finally, Western blot, CCK-8, Transwell, and Wound scratch were employed to validate LAMB1’s effect on NPC cells. Results: LAMB1 was highly expressed in NPC. High-expression LAMB1 was correlated with poorer progression-free survival and impeded the infiltration of CD4+ T-cells, CD8+ T-cells and dendritic cells. It also diminished the expression of HLA and suppressed T-cells stimulation. Differential expressed cytokines and involved pathways were divergent across different level of fibroblasts infiltration. At high level of fibroblasts, LAMB1 indirectly inhibited immune cells by remolding extracellular matrix. But at low level of fibroblasts, LAMB1 directly suppressed immune response. Tumors with high LAMB1 level had weak responses to immunotherapy. In vitro experiment, LAMB1 significantly suppressed HLA-1 and enhanced the proliferation, migration, and invasion capabilities of NPC cells. Conclusion: High expression of LAMB1 is significantly associated with an immune-suppressive tumor microenvironment in NPC. LAMB1 enhances the proliferation, migration and invasion of NPC cells. These findings suggest that LAMB1 may serve as a prognostic biomarker for predicting NPC progression and a potential therapeutic target to enhance the efficacy of existing immunotherapies. Level of evidence: 3.